DIGITALIZATION OF TAX ADMINISTRATION AND ITS IMPACT ON TAX DISCIPLINE OF COMPANIES - Mirkamol Sagdiev (Modern American Journals, 2025)
This article examines the main applications of nanotechnology in the jewellery industry: physical vacuum deposition (PVD), diamond-like carbon (DLC) coatings, and transparent nanobarrier layers. Their advantages over traditional rhodium and gold plating are highlighted, including increased wear resistance, corrosion resistance, luster and color retention, and the potential for creating new aesthetic effects.
Keywords: Nanotechnology, jewelry coatings, PVD, DLC, nanocomposites, wear resistance, corrosion resistance, decorative properties.